Risk Factors for Abnormal Developmental Trajectories in Young Children With Congenital Heart Disease. Issue 8 (25th August 2015) - Mussatto, Kathleen A.; Hoffmann, Raymond; Hoffman, George; Tweddell, James S.; Bear, Laurel; Cao, Yumei; Tanem, Jena; Brosig, Cheryl
<x xml:space="preserve">Abstract</x> Background— Children with congenital heart disease are at risk for developmental delay. This study sought to identify early risk factors for abnormal developmental trajectories in children with congenital heart disease. Methods and Results— Children with congenital heart disease at high risk for developmental delay, without known genetic abnormality, and with ≥3 assessments by the use of the Bayley Scales of Infant and Toddler Development, Third Edition, were studied. Logistic regression was used to assess the impact of patient and clinical factors on cognitive, language, and motor score trajectories; classified as: average or improved if all scores were ≥85 (<1 standard deviation below the mean) or increased to ≥85 and never decreased; or abnormal if all scores were <85, fell to <85 and never improved, or fluctuated above and below 85. Data on 131 children with 527 Bayley Scales of Infant and Toddler Development, Third Edition assessments were analyzed. Subject age was 5.5 to 37.4 months. Overall, 56% had cognitive, language, and motor development in the average range. Delays occurred in single domains in 23%. Multiple domains were delayed in 21%. More cardiac surgeries, longer hospital stay, poorer linear growth, and tube feeding were associated with worse outcomes in all domains (P<0.05). In the multivariable model, the need for tube feeding was a risk factor for having an abnormal developmental trajectory (odds ratio, 5.1–7.9). Minority race and lack of private insurance had significant relationships with individual domains. Conclusions— Longitudinal developmental surveillance identified early factors that can help quantify the risk of developmental delay over time. Strategies to improve modifiable factors and early therapeutic intervention can be targeted to children at highest risk.